Potential Uses of Electronic Fare Payment Records for Public Transit Agencies - Sahin, Ismail; Altun, Y. Batuhan (INST TRANSPORTATION ENGINEERS, 2007)
GROWING DEMANDS FOR PUBLIC TRANSPORTATION IN URBAN AREAS, SATISFYING CUSTOMER NEEDS AND EFFICIENT USE OF SCARCE RESOURCES REQUIRE THE ADOPTION OF EFFECTIVE PLANNING AND OPERATION METHODS AND THE IMPROVEMENT OF SERVICE PLANS THROUGH PERFORMANCE ANALYSIS. THIS FEATURE PRESENTS AN ALTERNATIVE WAY OF USING FARE DATA TO EXTRACT RIDERSHIP AND OPERATIONS INFORMATION TO BETTER MANAGE AND OPERATE TRANSIT SYSTEMS.
Keywords: Engineering; Transportation